Agglomeration of Invention in the Bay Area: Not Just ICT - Forman, Chris; Goldfarb, Avi; Greenstein, Shane (American Economic Review, 2016)
We document that the Bay Area rose from 4% of all successful US patent applications in 1976 to 16% in 2008. This is partly driven by the increase in the prevalence of information and communication technology; however, even for patents unrelated to information and communication technology, we see a disproportionate increase in the share of US patents from the Bay Area. We interpret this growth as a trend to coagglomeration in invention across technologies, and explore different dimensions of this trend.